Accommodating Purdah to the Workplace: Gender Relations in the Office Sector in Pakistan (The Pakistan Development Review, 1999)
Based on a qualitative survey of female office workers conducted in Lahore in 1996-97, this article examines the increasing market integration of women, particularly from the lower middle classes, into secretarial and technical occupations in the office sector in urban Pakistan. The study shows that gender images and gender relations inherent in the social order of Pakistani society—particularly the absence of socially sanctioned modes of communication between the sexes, a strong sexualisation of gender relations outside the kinship system, and the incessant harassment of women in the public sphere—surface inside the offices. Female office workers use many strategies, derived from their own life world, to maneuver in the office sector, to appropriate public (male) space, and to accommodate the purdah system to the office environment. By “creating social distance”, “developing socially obligatory relationships”, “integrating male colleagues into a fictive kinship system”, and “creating women’s spaces” they are able to establish themselves in a traditional male field of employment, namely, the office sector.